Matrix Effects of the Hydroethanolic Extract of Calyces of Physalis peruviana L. on Rutin Pharmacokinetics in Wistar Rats Using Population Modeling - Gina Paola Domínguez Moré; María Isabel Cardona; Paula Michelle Sepúlveda; Sandra Milena Echeverry; Cláudia Maria Oliveira Simões; Diana Marcela Aragón (MDPI AG, 2021)
Rutin is the rutinose conjugate of quercetin. It presents several biological activities and is the major flavonoid in the hydroalcoholic extract of the calyces of Physalis peruviana L. It also shows hypoglycemic activity after oral administration. The aim of this work was to study the matrix effects of the extract from P. peruviana calyces on the pharmacokinetics of rutin and its metabolites in Wistar rats, using non-compartmental and population pharmacokinetic analyses. A pharmacokinetic study was performed after intravenous and oral administration of different doses of pure rutin and the extract. In the non-compartmental analysis, it was found that rutin from the extract exhibited higher distribution and clearance, as well as an 11-fold increase in the bioavailability of its active metabolites. A population pharmacokinetic model was also carried out with two compartments, double absorption and linear elimination, in which the extract and the doses were the covariates involved. This model correctly described the differences observed between rutin as a pure compound and rutin from the extract, including the dose dependency.